2015
DOI: 10.1186/s12879-015-1260-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-kala-azar dermal leishmaniasis and leprosy: case report and literature review

Abstract: BackgroundPost-kala-azar dermal leishmaniasis (PKDL) is a dermal complication of visceral leishmaniasis (VL), which may occur after or during treatment. It has been frequently reported from India and the Sudan, but its occurrence in South America has been rarely reported. It may mimic leprosy and its differentiation may be difficult, since both diseases may show hypo-pigmented macular lesions as clinical presentation and neural involvement in histopathological investigations. The co-infection of leprosy and VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(84 reference statements)
1
15
0
1
Order By: Relevance
“…They showed that nodular PKDL was more likely (86%) and macular PKDL less likely (35%), resulted in infected sandflies as compared with VL (67%), and concluded that PKDL is nearly equally infectious as that of VL. This conclusion was consistent with the fact that PKDL patients go untreated for years due to scarcity of adequate diagnostic tools and resemblance with leprosy [2], accounting for their higher cumulative transmission potential than that of VL patients. Although the VL elimination program is on the verge of its accomplishment (1 case per 10000 persons per year), PKDL stands as a major obstacle as the contribution of PKDL cases nearly triples after intensive WHO interventions highlighting the need for prompt PKDL control program [152,153].…”
Section: Xenodiagnosissupporting
confidence: 83%
See 1 more Smart Citation
“…They showed that nodular PKDL was more likely (86%) and macular PKDL less likely (35%), resulted in infected sandflies as compared with VL (67%), and concluded that PKDL is nearly equally infectious as that of VL. This conclusion was consistent with the fact that PKDL patients go untreated for years due to scarcity of adequate diagnostic tools and resemblance with leprosy [2], accounting for their higher cumulative transmission potential than that of VL patients. Although the VL elimination program is on the verge of its accomplishment (1 case per 10000 persons per year), PKDL stands as a major obstacle as the contribution of PKDL cases nearly triples after intensive WHO interventions highlighting the need for prompt PKDL control program [152,153].…”
Section: Xenodiagnosissupporting
confidence: 83%
“…Based on its clinical manifestations, this disease occurs into self-healing cutaneous leishmaniasis (CL), skin mucosal ulcers forming mucocutaneous leishmaniasis (MCL), and fatal visceral leishmaniasis (VL), which may be followed by a dermal sequel called PKDL. PKDL, which can be confused with leprosy [ 2 ], develops after six months and sometimes up to 5 years following the previous VL incidence, and 15% of PKDL cases have shown no prior kala-azar infection [ 3 ]. But a hospital-based retrospective study on Indian PKDL subjects showed that 20% of cases had no antecedent of VL [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fever, weight loss, fatigue, and anemia are primary stages, accompanied with enlargement of spleen the most common feature then swelling of liver but not as severe as in spleen and lymph nodes; this is the characteristic of African Kala-azar. Meanwhile, Chinese type is well known for causing inflammation of nodes [51]. PKDL skin damage commonly seen on the face, hands, feet and abdomen.…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…PKDL skin damage commonly seen on the face, hands, feet and abdomen. Familiar features of "Black Sickness" such as in South Sudan and Sudan as in Figure 6 above [51].…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…21,72 Sob o ponto de vista clínico e epidemiológico, ressalta-se também a importância da definição do agente causador de tal moléstia, diante do encontro de outros tripanossomatídeos que não leishmânias, no vetor das leishmanioses, os flebotomíneos, 83 bem como de haver na literatura descrição de manifestações cutâneas relacionadas com a lesão dérmica pós-calazar (PKDL) envolvendo L. (L.) infantum. 26 Portanto, casos de leishmaniose tegumentar (LT) causada por essa espécie fora do Velho Mundo, inclusive no Brasil, 11,82 já foram descritos, como também, caso de LV causada por espécie dermotrópica. 5 Assim como manifestações incomuns de leishmaniose causada por L. (L.) infantum, também foram descritos casos de coinfecção de espécies causadoras de LT e LV.…”
Section: Kdna Pcr Rv1-rv2unclassified